Integrating HIV/AIDS services into financial protection systems to increase sustainability of the HIV/AIDS response - Judy Chang; Mai Hijazi; Susanna Baker; Onyeka Igboelina; Carlyn Mann; Hannah Marqusee; Cam Anh Nguyen; Carolina Piña; Jemeh Pius; Robert Stanley; Zacheaus Zeh Akiy (BMC Health Services Research)
Abstract Begun in 2014, the Sustainable Financing Initiative (SFI) was dedicated to mobilizing domestic resources for the HIV response. Among its three programmatic pillars was a focus on ensuring financial protection for people living with HIV (PLHIV). SFI’s activities were founded on a strong understanding of and alignment with partner government priorities, as well as costing and actuarial analyses, which allowed for the development of context-specific approaches for improving financial protection for PLHIV. SFI implemented financial protection activities in a total of nine countries; the five countries with the most substantial investments are discussed in this paper. In Vietnam, SFI’s support helped the country to integrate almost all outpatient HIV treatment facilities into the public health system, attain enrollment of 90% of PLHIV into Social Health Insurance (SHI), and increase domestic funding for HIV through SHI. In Cambodia, SFI supported the development of a guiding framework for integration of HIV/AIDS services into the existing health system; key achievements included a policy change that expanded eligibility for the country’s Health Equity Fund, allowing all PLHIV to access free health services. In the Dominican Republic, SFI support led to the inclusion of antiretroviral drugs in the family health insurance benefit package, increased enrollment of PLHIV in health insurance, and expanded care options through non-governmental organizations. In Nigeria, SFI’s support helped to enroll more than 600,000 people and empanel 216 health facilities into the Lagos State Health Insurance Scheme. In Cameroon, SFI support helped the government achieve stepwise progress on key building blocks of its planned new universal health coverage system; SFI contributed to the development of a consolidated package of services, standardized care and service protocols, and accreditation criteria. SFI’s investments in financial protection demonstrated that with strong political will; long-term engagement with partner governments; and focused technical assistance for advocacy, policy reform, and implementation support, HIV services can be successfully integrated into financial protection systems. Such integration can promote increased, long-term domestic financing for HIV while also protecting PLHIV from financial risk.